Invitro Antidiabetic Potential of Hydroethanolic Leaf Extract of Luffa Acutangula (L.) - Shanmuga Priya R; Ragavan B (International Journal of Pharma and Bio Sciences, 2020)
Diabetes mellitus is a group of heterogeneous disorders which arises due to glucose intolerance associated with disagreements in series of metabolism like carbohydrate, protein and lipids. These metabolic alterations emanate from diminished insulin secretion or action and sometimes both. The aim of the present study is to investigate the in-vitro antidiabetic potential of Luffa acutangula leaves of which the study done mainly on the inhibitory potential of carbohydrate hydrolysing enzyme α-amylase and α-glucosidase. The key strategy behind antidiabetic medication is inhibition of these 2 enzymes. There is a significant increase in inhibitory potential of enzyme α-amylase and α-glucosidase in a dose dependent manner with IC50 value 244.5 µg/ml and 673.4 µg/ml with that of standards metformin and acarbose respectively. This result evidenced the potent antidiabetic activity of Luffa acutangula leaves. Thus, it could be concluded that the presence of rich phenolic compounds might be responsible for the management of diabetes. Hence further quantification of specific phytoconstituents responsible for inhibitory activity and its efficacy in animals and humans should be done through in-vivo studies for clinical applications.